Photosynthetic profiling of a Dunaliella salina mutant DS240G-1 with improved β-carotene productivity induced by heavy ions irradiation - Xi, Yimei; Liu, Ying; Chi, Zhanyou; Yin, Liang; Wang, Lijuan; Luo, Guanghong (International Journal of Agricultural and Biological Engineering, 2021)
Carbon-ion irradiation is a technique for trait improvement in the microalgae, but the underlying mechanisms that how it altered the biomass, and photosynthetic pigments accumulation were unclear. One mutant (DS240G-1) was obtained from Dunaliella salina by heavy ion irradiation mutagenesis. Compared to the wild type, the biomass accumulation and maximum growth rate of DS240G-1 were increased by 34% and 55% respectively, and its β-carotene content was 21% higher than the wild type. Subsequent analysis of the chlorophyll fluorescence parameters indicated that higher β-carotene productivity was likely owing to the improved maximum quantum efficiency (Fv/Fm) and decreased thermal dissipation of photosynthesis in DS240G-1 than that of wild type during cultivation. In addition, the result of this study revealed that high content of ROS may induce β-carotene accumulation in mutant DS240G-1. Also, the total fatty acid (TFA) content in mutant DS240G-1 was 79% higher than that in wild type. Owing to its high β-carotene productivity and total fatty acid content, DS240G-1 could be considered as a promising candidate for microalgae β-carotene and biodiesel production. This work provided the first insight into the biological effects involved in carbon-ions irradiation on the photosynthetic activity of D. salina. Keywords: microalgae, D. salina, carbon-ions irradiation, chlorophyll fluorescence, β-carotene DOI: 10.25165/j.ijabe.20211402.5993 Citation: Xi Y M, Liu Y, Chi Z Y, Yin L, Wang L J, Luo G H. Photosynthetic profiling of a Dunaliella salina mutant DS240G-1 with improved β-carotene productivity induced by heavy ions irradiation. Int J Agric & Biol Eng, 2021; 14(2): 211–217.